Cosmic-ray generated bubbles around their sources. Issue 1 (21st February 2022) - Schroer, B; Pezzi, O; Caprioli, D; Haggerty, C C; Blasi, P
ABSTRACT: Cosmic rays (CRs) are thought to escape their sources streaming along the local magnetic field lines. We show that this phenomenon generally leads to the excitation of both resonant and non-resonant streaming instabilities. The self-generated magnetic fluctuations induce particle diffusion in extended regions around the source, so that CRs build up a large pressure gradient. By means of two-dimensional (2D) and three-dimensional (3D) hybrid particle-in-cell simulations, we show that such a pressure gradient excavates a cavity around the source and leads to the formation of a cosmic ray dominated bubble, inside which diffusivity is strongly suppressed. Based on the trends extracted from self-consistent simulations, we estimate that, in the absence of severe damping of the self-generated magnetic fields, the bubble should keep expanding until pressure balance with the surrounding medium is reached, corresponding to a radius of ∼10–50 pc. The implications of the formation of these regions of low diffusivity for sources of Galactic CRs are discussed. Special care is devoted to estimating the self-generated diffusion coefficient and the grammage that CRs might accumulate in the bubbles before moving into the interstellar medium. Based on the results of 3D simulations, general considerations on the morphology of the γ-ray and synchrotron emission from these extended regions also are outlined.